Delayed-onset chloroquine retinopathy. Issue 4 (April 1986) - Ehrenfeld, M; Nesher, R; Merin, S
Abstract : Delayed-onset chloroquine retinopathy was diagnosed in a patient seven years after cessation of treatment by a total dose of 730 g of chloroquine for rheumatoid arthritis. Visual functions continued to deteriorate after the diagnosis. Periodic examinations by ophthalmoscopy and by functional tests such as EOG and visual fields should be continued in patients at risk of delayed-onset chloroquine retinopathy after discontinuance of the drug.